Pengujian dan Penentuan Spesies Gastropoda sebagai Bioindikator di Kawasan Reboisasi Mangrove Kepulauan Seribu, Indonesia - Syahrial Rial; Muhammad Fauzan Isma; Ahmad ryadi; M. Ilham Fajriansyah (Journal of Marine Research and Technology, 2020)
The development of coastal zones throughout the world has resulted in changes in the order of the mangrove ecosystem, therefore, planting activities are carried out in various regions. The study of the testing and determination of gastropod species as bioindicators in the mangrove reforestation area was carried out in the Seribu Islands. This research aims to determine how suitable the gastropod species are used as bioindicators in assessing the success of mangrove reforestation, especially in the Seribu Islands. Collection of gastropod species is done by making line transects and plots drawn from the reference point (outermost mangrove stands) and perpendicular to the coastline to the mainland. Line transects are made of plots of size 10 x 10 m and in the size of 10 x 10 m a small plot of 1 x 1 m is made. Furthermore, testing is carried out with several criteria and analyzed using multivariate Principal Component Analysis (PCA) statistics. The results of the study show that the species Littoraria scabra has met all the specified testing criteria. Then L. scabra also has the highest eigenvalue compared to the other species, making it suitable to be used as a bioindicator species in assessing the success of the Seribu Islands mangrove reforestation.